Cladorhiza corallophila sp. nov., a new carnivorous sponge (Cladorhizidae, Demospongiae) living in close association with Lophelia pertusa and Madrepora oculata (Scleractinia) - Göcke, Christian; Hestetun, Jon T.; Uhlir, Carolin; Freiwald, André; Beuck, Lydia; Janussen, Dorte (Zootaxa, 2016)
In this study, we describe a new species of cladorhizid sponge, which shows a very peculiar mode of life: It always occurs in association with the scleractinian cold-water corals Lophelia pertusa and Madrepora oculata. Although the sponge lives in nutrient-rich areas, we document its carnivorous feeding behavior. The identity of the new species was verified using molecular markers: the species is very closely related to the North-Atlantic Cladorhiza abyssicola, but it differs distinctly, and forms a monophyletic clade. The two species might be considered very close relatives, probably sister species deriving from a common ancestor.